PENERAPAN MODEL PROJECT BASED LEARNING TERHADAP PENINGKATAN PEMAHAMAN KONSEP SISWA PADA MATERI SISTEM PERNAPASAN MANUSIA: Penelitian Tindakan Kelas - Mutia, Zulfa; Marnita; Hanum, Erlia (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The low level of students’ conceptual understanding of the human respiratory system indicates the need for a learning model that promotes active student engagement in the learning process. This study aimed to improve students’ conceptual understanding through the implementation of the Project Based Learning (PjBL) model on the topic of the human respiratory system in Grade V at SD Negeri 2 Bandar Dua. This research employed Classroom Action Research (CAR), conducted in two cycles, each consisting of planning, action, observation, and reflection stages. The participants were 15 fifth-grade students. Data were collected through achievement tests, observations of teacher and student activities, and student response questionnaires. The data were analyzed descriptively by calculating the percentages of learning mastery, learning activities, and student responses. The findings revealed that the implementation of Project Based Learning effectively improved students’ conceptual understanding. Learning mastery increased from 26.6% in Cycle I to 86.7% in Cycle II. Teacher activity improved from the good to the very good category, with percentages ranging from 84.7% to 94.0%, while student activity increased from the fair to the very good category, with percentages ranging from 74.4% to 92.2%. Furthermore, 95.08% of students expressed highly positive responses to the implementation of Project Based Learning. Therefore, the Project Based Learning model is effective in enhancing students’ conceptual understanding while fostering a more active, collaborative, and meaningful learning environment in elementary science education